Fostering Self-Directed Learning through Local Wisdom Project-Based Learning - Rosmayanti, Vivit; Sukmawati, Sukmawati; Mohamed, Sheik; Sujarwo, Sujarwo; Amin, Sulvahrul (Journal of Language Learning and Assessment, 2024)
Purpose This study aims to enhance the efficacy of Local Wisdom Problem-Based Learning (LWPBL) in fostering students' Self-Directed Learning (SDL). The PjBL elements proposed by Larmer and Mergendoller include Providing a problem, Involvement in the inquiry process, Authenticity, Students' Voice, Reflection, Critique and Revision, and Public Product were adopted.   Methodology To accomplish the research goals, questionnaires were employed as the primary means of data gathering and disseminated to a sample of 100 students from four public high schools in South Sulawesi, who were taught using the LWPjBL method in their English class. The samples were chosen using the quota sampling technique. Garrison’s model of the Self-Directed Learning Aptitude Scale (SDLAS) was used to measure the student’s aptitude for SDL. The data were analyzed using Partial Least Squares (PLS).   Results/Findings The findings of this study indicated that the eight elements mentioned above, have a favorable impact on students' SDL. The result of data analysis indicated that 98% of the eight elements could explain the influence on students’ SDL.   Implications The LWPjBL is strongly recommended for teachers, particularly those teaching English in high schools, to enhance the student’s learning experience and SDL.